Valorizations Environmental, Energy And Agronomic Of Biomethanisation Industrial Of The Avicolous Biomass - M’sadak, Y.; Ben M’barek, A. (University of Eloued جامعة الوادي, 2015)
This work consists in studying the anaerobie fermentation of the avicolous droppings on the level a digester pilot industrial. It was interested towards substitution partial of Forestry Compost (FC), produces locally in one seedbed except ground, by the avicolous methacompost refined in its two states, namely at the exit of decanter (AMCA) and at the exit of digester (AMCA') according one rate of 20%. The synthesis of the principal results is: the best assessments of depollution are obtained on the level of the mud tank as well concerning SM and DBO5; the incorporation of the avicolous methacompost with FC has a remarkable positive effect on germination, and consequently, on the growth of the seedlings of Acacia cyanophylla, in terms of height and of diameter; the best results of growth in height and diameter correspond to the mixture 80% FC + 20% AMCA'.
Articale in Journal of fundamental and Applied Sciences Vol. 07 N. 01
Keywords: Biomethanisation industrial avicolous ; assessments of depollution ; gas composition ; calorific value ; methacompost avicolous ; substrate of culture.